PENGARUH SISTEM PENGENDALIAN INTERN, PENYAJIAN LAPORAN KEUANGAN, AKSESIBILITAS LAPORAN KEUANGAN DAN GAYA KEPEMIMPINAN TERHADAP TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN INDRAGIRI HULU - Sari, Embun Widya; Azlina, Nur; ', Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the effect of the internal control system to optimize transparency and accountability in financial management, financial statements to optimize transparency and accountability in financial management, accessibility to optimize transparency and accountability in financial management and style of leadership to optimize transparency and accountability in financial management. In this study population used are all employees in all SKPD in Indragiri Hulu 29 SKPD, the sampling technique used in this research is purposive sampling technique. The criteria used are limited only SKPD samples that make the Regional Financial Statements as many as 29 SKPD. Furthermore, from each SKPD that the research samples were taken three people consisting of the Head of Department, Head of Finance and 2 staff of finance, in order to obtain the amount of sample as many as 87 people. Based on the results obtained from the data analysis, it can be concluded as follows: Internal Control System (SPI) and accessibility affect the transparency and accountability of financial management in govermental institution at Indragiri Hulu Regency. While presenting the financial statements and the leadership style does not affect the transparency and accountability of financial management in govermental institution at Indragiri Hulu Regency.Keywords: Internal Control System, Financial Statements, Accessibility, Leadership Style, Transparency and Accountability